Intestinal Staphylococcus spp. and virulent features associated with coeliac disease - Sánchez, Ester; Ribes-Koninckx, Carmen; Calabuig, Miguel; Sanz, Yolanda (Journal of clinical pathology, 2012)
AimTo determine whether intestinal Staphylococcus spp. and their pathogenic features differed between coeliac disease (CD) patients and healthy controls.Methods60 children, including active CD (n=20) and non-active CD (n=20) patients and healthy controls (n=20), were studied. Staphylococci were isolated from faeces and identified by PCR and DNA sequencing. The carriage of virulent genes, including adhesion (atlE and fbe), cell aggregation (icaD), global regulatory (agr and sar) and methicillin-resistant (mecA) genes, was analysed by PCR.ResultsStaphylococcus epidermidis was more abundant in the microbiota of active and non-active CD patients than in controls. Staphylococcus haemolyticus was more abundant in active CD patients than in control subjects. Staphylococcus aureus was less abundant in active CD patients than in the other child groups. Staphylococcus spp. diversity was higher in active CD patients than in non-active CD patients and controls. The presence of the mecA gene and the simultaneous presence of both the mecA and atlE genes were higher in S. epidermidis clones isolated from CD patients, with active and non-active disease, than in those from control subjects. The individual presence of the other virulent genes was lower in S. epidermidis from active CD patients than in those from the other -child- groups.ConclusionsIncreased abundance of S. epidermidis carrying the mecA gene, in active and non-active CD patients, most likely reflects increased exposure of these subjects to opportunistic pathogens and antimicrobials.